Diagnóstico e avaliação ambiental das nascentes da Serra dos Matões, município de Pedro II, Piauí - Gomes, Érico Rodrigues [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The Pedro II municipality, 195 km far from Teresina, Piauí, is situated in the foothills of the Matões Mountains, forming a water divider of the Longá river watershed (water spring of the Corrente, Matos, Caldeirão and Piracuruca rivers) and Poti (water springs of Capivara and Parafuso rivers). This area is the recharge zone of the Cabeças aquifer which has high water production with insurgents mechanisms, responsible for supply of many villages. Due to its local importance, and the need for its preservation, that's why this study has as objective, to make the diagnosis and assessment of environmental impacts on water springs found in the surroundings of the Matões mountains. The field trips were preceded by the acquisition and processing of satellite images, maps and literature review. The diagnosis came from in loco observations, along with a photo documentary, between the years of 2012 to February 2015, with 525 described points in 64 water springs. In the laboratory stage was carried out processing of data obtained during the previous step, with production of maps and data integration. The analysis and environmental assessment were based on the methods of Listing Control, Matrix of aspects x results, and an unprecedented proposal of macroscopic environmental assessment of water springs. As a result, were identified 18 activities causing 57 environmental impacts, enabling the characterization of water resources, soil, topography, climate, air quality and noise, fauna, flora, infrastructure, standard of living, culture and economy. The water springs Environmental Quality Index shows that 45% of the studied water springs are evaluated as Preserved, 52% moderately preserved and 3% as degraded. This data set allowed the proposition of a project of environmental recovery and preservation of water springs, considering the involvement of various social actors, use and occupation of soil, restriction of installation of potentially...

O município de Pedro II, a 195 km de Teresina, Piauí, está situado no contraforte da Serra dos Matões, formando um divisor de águas das bacias hidrográficas dos rios Longá (nascentes dos rios Corrente, dos Matos, Caldeirão e Piracuruca) e Poti (nascentes dos rios Capivara, Parafuso). Essa área constitui a zona de recarga do aquífero Cabeças que apresenta elevada produção de água com mecanismos surgentes, responsáveis pelo abastecimento de inúmeros povoados. Devido à sua importância local e à necessidade de sua preservação, é que o presente estudo tem como objetivo, realizar o diagnóstico e a avaliação dos impactos ambientais nas nascentes encontradas no entorno da Serra dos Matões. As expedições ao campo foram antecedidas pela aquisição e tratamento de imagens de satélite, mapas e revisão bibliográfica. O diagnóstico ocorreu a partir de observações in loco, juntamente com um documentário fotográfico, entre os anos de 2012 a fevereiro de 2015, com 525 pontos descritos em 64 nascentes. Na etapa de laboratório, foi realizado o tratamento das informações obtidas durante a etapa anterior, com geração de mapas e integração de dados. A análise e avaliação ambiental foram baseadas nos métodos da Listagem de Controle, Matriz de causa x efeito e em proposta inédita de Avaliação Ambiental Macroscópica das Nascentes. Como resultado, foram identificadas 18 atividades responsáveis por 57 impactos ambientais, possibilitando a caracterização dos recursos hídricos, solo, relevo, clima, qualidade do ar e ruído, fauna, flora, infraestrutura, nível de vida, cultura e economia. O Índice de Qualidade Ambiental das Nascentes mostra que 45% das nascentes estudadas são avaliadas como Preservadas, 52% são Moderadamente Preservadas e 3% como Degradadas. Esse conjunto de dados permitiu a proposição de um projeto de recuperação e preservação ambiental das nascentes, considerando o envolvimento de diversos...
Keywords: Ecology; Ecologia; Agua - Conservação; Água - Abastecimento; Proteção ambiental; Bacias hidrograficas; Nascentes; Geoprocessamento; Piaui